Chemical fire and explosion hazards at seaports: a review of human – causes, consequences and prevention strategies - Ван Нам Нго; Хуу Хиеу Нгуен; Ань Фан (Вестник Университета гражданской защиты МЧС Беларуси)
Purpose. Seaports serve as critical centers for global trade and transportation; however, they are also prone to significant risks of chemical fire and explosion accidents. The purpose of this paper is to examine the human-related causes, consequences, and prevention strategies associated with these hazards at seaports, while addressing their potential to cause severe casualties, environmental harm, economic losses, and social disruption.